68Ga-FAPI PET/CT in Thyroid Cancer With Thyroglobulin Elevation and Negative Iodine Scintigraphy. (May 2021) - Fu, Hao; Fu, Jie; Huang, Jingxiong; Su, Xinyi; Chen, Haojun
Abstract : Abstract: Differentiated thyroid cancer with thyroglobulin elevation and negative iodine scintigraphy (TENIS) syndrome is a diagnostic and therapy dilemma. In this study, we present a case of TENIS with detectable metastases in the larynx and lung on the CT scan. 68 Ga-fibroblast activation protein inhibitor (FAPI) PET/CT was performed for further detection of tumor recurrence and metastases, which showed intense 68 Ga-FAPI activity in the metastatic lesions. To the best of our knowledge, this is the first case of TENIS presenting with FAPI-avid metastatic lesions, demonstrating its usefulness for localizing recurrent or metastatic lesions in patients with TENIS.